2021
DOI: 10.3390/genes12101561
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Transcriptome Analysis Reveals Dynamic Expression Profiles of Gametes and Embryonic Development in Japanese Flounder (Paralichthys olivaceus)

Abstract: The maternal-to-zygotic transition (MZT) is a crucial event in embryo development. While the features of the MZT across species are shared, the stage of this transition is different among species. We characterized MZT in a flatfish species, Japanese flounder (Paralichthys olivaceus). In this study, we analyzed the 551.57 GB transcriptome data of two types of gametes (sperms and eggs) and 10 embryo developmental stages in Japanese flounder. We identified 2512 maternal factor-related genes and found that most of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 46 publications
0
1
0
Order By: Relevance
“…This study generated high-quality RNA-seq data for C. semilaevis gametes (sperm and oocyte) and early embryos at different developmental stages (from the four-cell to gastrula stages) to track the global gene expression changes during early embryogenesis. For the first time, we confirmed that large-scale ZGA occurs at the blastula stage in C. semilaevis, consistent with the findings for Japanese flounders [44], zebrafish, and frogs [4]. Accordingly, gene transcripts that were abundant in C. semilaevis oocytes were also abundant in four-cell to one thousand-cell embryos, which conferred functions that are vital for pre-ZGA cleavage (e.g., the enrichment of mitosis-related genes in the Maternal module).…”
Section: Discussionsupporting
confidence: 90%
“…This study generated high-quality RNA-seq data for C. semilaevis gametes (sperm and oocyte) and early embryos at different developmental stages (from the four-cell to gastrula stages) to track the global gene expression changes during early embryogenesis. For the first time, we confirmed that large-scale ZGA occurs at the blastula stage in C. semilaevis, consistent with the findings for Japanese flounders [44], zebrafish, and frogs [4]. Accordingly, gene transcripts that were abundant in C. semilaevis oocytes were also abundant in four-cell to one thousand-cell embryos, which conferred functions that are vital for pre-ZGA cleavage (e.g., the enrichment of mitosis-related genes in the Maternal module).…”
Section: Discussionsupporting
confidence: 90%
“…This method could dynamically monitor plant responses to different stages of stimuli exposure at the gene expression level. For example, it has previously been used to reveal how wheat can coordinate the expression of homologous genes to cope with various environmental constraints at the genome-wide level ( Hao et al., 2021 ); how candidate genes regulate flower opening and closing in Iris, leading to an improved understanding of the regulatory network of flowering ( Liu et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%